A first scoring approach for evaluating the European Ocean Observing Community - Hassoun, Abed El Rahman; Tanhua, Toste; Heslop, Emma; Lips, Inga; Álvarez, Marta; Petihakis, George; García-Ibáñez, Maribel I.; Velaoras, Dimitris; Giani, Michele; Bange, Hermann W.; Lønborg, Christian; Karstensen, Johannes (Frontiers in Marine Science, 2024)
The European Ocean Observing Community (EOOC) integrates inputs from diverse entities dedicated to comprehensively monitoring and forecasting oceanic phenomena in European Seas. With increasing climate and anthropogenic pressures, the urgency of ensuring the EOOC’s preparedness to observe Essential Ocean Variables (EOVs) is evident. This paper advocates for the adoption of a scoring approach designed to evaluate the readiness of the EOOC in observing and forecasting key ocean phenomena. The proposed scoring methodology can be applied at both European and potentially regional and/or national levels, and emerges as a transformative tool for scrutinizing the EOOC’s capability to predict and monitor key ocean phenomena. Our findings, based on the application of the scoring approach, suggest that while the community demonstrates commendable readiness levels for certain oceanic phenomena, 83% remain in developing stages, oscillating between “Idea” and “Trial” readiness levels. A closer examination exposes critical shortages predominantly in the coordination and observational facets (Process), and data management and information products (Output). The implications of these identified gaps reach far beyond academic realms, profoundly affecting diverse sectors and societal resilience (e.g., energy sector). The suggested scoring approach serves as a clear call for strategic investments and heightened support for the European observing community. By adopting a regular and systematic scoring methodology, we not only measure progress at present but also pave the way for a resilient and future-ready EOOC.